PENGEMBANGAN KARAKTER RELIGIUS SISWA MELALUI PENERAPAN CONTEXT RICH PROBLEMS YANG TERINTEGRASI DALAM PEMBELAJARAN KIMIA PADA MATERI IKATAN KIMIA - Sri Wahyuni; Khaeruman Khaeruman; Yusran Khery (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2014)
The concept of chemistry is difficult and complicated because it is abstract. Students are encouraged to have a religious mindset. The current learning process in chemistry subjects is still teacher-centered. Different students' understanding needs to be addressed. Therefore, low-ability students can not understand the concepts; consequently the students' learning outcomes and mindset are less religious while learning chemistry. An effort for students to think religiously and improve student learning outcomes is through the use of learning methods and adequate learning resources to improve learning activities and students more active in the learning process. This problem can be solved by developing the 'religious character' of students through the application of Context Rich Problems. This research is PTK (class action) with qualitative and quantitative approach. This research was conducted in MA Nahdlatus Shaufiah Wanasaba. Sampling using simple technique. The sample of the research is the students of class X. The results show that, the religious character and learning outcomes from cycle to cycle have increased. The average score of the students' religious characters in the first cycle was 66.67% and the second cycle was 94.63%. The completeness of each learning outcomes in the first cycle is 44.44% and cycle II is 92.59%. We conclude that the development of the religious character of the students through the application of integrated Context Rich Problems can be used as an alternative to enhance the ability of religious character and student learning outcomes.